Is the Prosthetic Homologue Necessary for Embodiment? - Dornfeld, Chelsea; Swanston, Michelle; Cassella, Joseph; Beasley, Casey; Green, Jacob; Moshayev, Yonatan; Wininger, Michael (Frontiers in Neurorobotics, 2016)
Embodiment is the process by which patients with limb loss come to accept their peripheral device as a natural extension of self. However, there is little guidance as to how exacting the prosthesis must be in order for embodiment to take place: is it necessary for the prosthetic hand to look just like the absent hand? Here, we describe a protocol for testing whether an individual would select a hand that looks like their own from among a selection of 5 hands, and whether the hand selection (regardless of homology) is consistent across multiple exposures to the same (but reordered) set of candidate hands. Pilot results using healthy volunteers reveals that hand selection is only modestly consistent, and that selection of the prosthetic homologue is atypical (61 of 192 total exposures). Our protocol can be executed in minutes, and makes use of readily available equipment and softwares. We present both a face-to-face and a virtual protocol, for maximum flexibility of implementation.